Giving effective feedback : (Harvard Business Review Press, 2014)
Don't have much time? Get up to speed fast on the most essential business skills with HBR's 20-Minute Manager series. Whether you need a crash course or a brief refresher, each book in the series is a concise, practical primer that will help you brush up on a key management topic. Advice you can quickly read and apply, for ambitious professionals and aspiring executives--from the most trusted source in business.